2021
DOI: 10.1099/jmm.0.001456
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen cases of severe pneumonia caused by Chlamydia psittaci in South China investigated via metagenomic next-generation sequencing

Abstract: Introduction. Chlamydia psittaci is an important cause of community-acquired pneumonia (CAP). The spectrum of CAP due to Chlamydia psittaci ranges from mild, self-limited to acute respiratory failure and the early identification of this disease can be challenging. Metagenomic next-generation sequencing (mNGS) of bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Chest imaging indicates predominantly consolidated lung lesions, and respiratory distress and respiratory failure can develop rapidly in most severely ill patients, with some patients presenting ARDS and even multiple organ system failure. 8,9 In the present case, the disease progressed rapidly after onset, and respiratory failure, ARDS, and severe liver and kidney failure developed within a short period. However, the patient had a good prognosis after timely and accurate diagnosis and treatment, suggesting that early and accurate treatment is essential for improving prognosis.…”
Section: Discussionmentioning
confidence: 49%
“…Chest imaging indicates predominantly consolidated lung lesions, and respiratory distress and respiratory failure can develop rapidly in most severely ill patients, with some patients presenting ARDS and even multiple organ system failure. 8,9 In the present case, the disease progressed rapidly after onset, and respiratory failure, ARDS, and severe liver and kidney failure developed within a short period. However, the patient had a good prognosis after timely and accurate diagnosis and treatment, suggesting that early and accurate treatment is essential for improving prognosis.…”
Section: Discussionmentioning
confidence: 49%
“… 16 With the widespread use of mNGS in the clinic, its use to diagnose C. psittaci pneumonia has increased. 8 , 10 , 11 , 17–20 All patients in the present study were diagnosed with C. psittaci infection solely using mNGS. Among the samples that were positive for C. psittaci detected using mNGS, three ompA fragments (1.4 kb) were successfully amplified and sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…16 With the widespread use of mNGS in the clinic, its use to diagnose C. psittaci pneumonia has increased. 8,10,11,[17][18][19][20] All patients in the present study were diagnosed with C. psittaci https://doi.org/10.2147/IDR.S393195…”
Section: Discussionmentioning
confidence: 99%
“…Psittacosis is diagnosed by real-time polymerase chain reaction (RT-PCR) or serology based on clinical suspicions, and many recent studies (8)(9)(10)(11)(12) have reported the use of mNGS on the diagnosis of psittacosis. The mNGS of BALF (5) has the potential to improve pathogen identification in severe pneumonia, and it is widely used in identifying pathogens, especially in severe cases.…”
Section: Discussionmentioning
confidence: 99%